The Influence of School Facilities and Technology on The Demand for Teacher Workforce in Private High School in Jambi City - Kuswanto Kuswanto; Mukhammad Kundori; Muhammad Arif Liputo (Universitas Negeri Semarang, 2025)
This study aims to analyze the influence of school facilities and technology on the demand for teacher labor. The study was conducted at 21 private high schools in Jambi City. This study uses quantitative methods in collecting and analyzing the data needed to answer the research questions. Data were analyzed using multiple regression statistical techniques. Based on the analysis, it shows that the school facility variable has a positive and significant effect on the demand for labor in the education sector. The more school facilities used by educational institutions, the higher the need for teacher labor used by the school. The technology variable has a positive and significant effect on the demand for labor in the education sector. The better the use of technology in managing schools, the more it will optimize the role of each sector in the school so that it will increasingly require the role of teacher labor. The regression model produced statistically has a fairly high ability to predict the effect of school facilities and technology on the demand for labor in the education sector because it is supported by an R-square value of 60.4%. Based on these findings, it is clear that good management of school facilities and technology will have an impact on increasing the demand for labor in the education sector.